Accelerating Heat-Initiated Radical Reactions of Organic Halides with Tin Hydride Using Flow Microreactor Technologies - Jiang, Yiyuan; Ashikari, Yosuke; Guan, Kaiteng; Nagaki, Aiichiro (Synlett, 2020)
We herein report that flow microreactors can promote an efficiency of radical chain reactions. The chain reactions with a fast propagation step can be accelerated by virtue of an efficient heat-transfer character of the microreactors, whereas the yield of those reactions with a slow propagation step was increased by flow microreactors. Moreover, the yield was further increased by a sequential addition of the initiators, which was allowed by a flow-sequential-addition system.
Keywords: flow microreactor; flow chemistry; radical chain reduction; reaction acceleration; sequential addition